Multiparametric whole-body 3.0-T MRI in newly diagnosed intermediate- and high-risk prostate cancer: diagnostic accuracy and interobserver agreement for nodal and metastatic staging - Johnston,EW; Latifoltojar,A; Sidhu,HS; Ramachandran,N; Sokolska,M; Bainbridge,A; Moore,C; Ahmed,HU; Punwani,S (European Radiology, 2019)
OBJECTIVES: To determine the diagnostic accuracy and interobserver concordance of whole-body (WB)-MRI, vs. 99mTc bone scintigraphy (BS) and 18fluoro-ethyl-choline (18F-choline) PET/CT for the primary staging of intermediate/high-risk prostate cancer. METHODS: An institutional review board approved prospective cohort study carried out between July 2012 and November 2015, whereby 56 men prospectively underwent 3.0-T multiparametric (mp)-WB-MRI in addition to BS (all patients) ± 18F-choline PET/CT (33 patients). MRI comprised pre- and post-contrast modified Dixon (mDixon), T2-weighted (T2W) imaging, and diffusion-weighted imaging (DWI). Patients underwent follow-up mp-WB-MRI at 1 year to derive the reference standard. WB-MRIs were reviewed by two radiologists applying a 6-point scale and a locked sequential read (LSR) paradigm for the suspicion of nodal (N) and metastatic disease (M1a and M1b). RESULTS: The mean sensitivity/specificity of WB-MRI for N1 disease was 1.00/0.96 respectively, compared with 1.00/0.82 for 18F-choline PET/CT. The mean sensitivity and specificity of WB-MRI, 18F-choline PET/CT, and BS were 0.90/0.88, 0.80/0.92, and 0.60/1.00 for M1b disease. ROC-AUC did not show statistically significant improvement for each component of the LSR; mean ROC-AUC 0.92, 0.94, and 0.93 (p < 0.05) for mDixon + DWI, + T2WI, and + contrast respectively. WB-MRI had an interobserver concordance (κ) of 0.79, 0.68, and 0.58 for N1, M1a, and M1b diseases respectively. CONCLUSIONS: WB-MRI provides high levels of diagnostic accuracy for both nodal and metastatic bone disease, with higher levels of sensitivity than BS for metastatic disease, and similar performance to 18F-choline PET/CT. T2 and post-contrast mDixon had no significant additive value above a protocol comprising mDixon and DWI alone. KEY POINTS: • A whole-body MRI protocol comprising unenhanced mDixon and diffusion-weighted imaging provides high levels of diagnostic accuracy